Breast cancer biomarker (HER2-ECD) detection using a molecularly imprinted electrochemical sensor - Pacheco, João (2019)
The extracellular domain of the human epidermal growth factor receptor 2 (HER2-ECD) is a protein breast cancer biomarker. Its quantification in peripheral blood could provide an important contribution to diagnostics and patient follow-up. In this work an electrochemical molecularly imprinted polymer (MIP) sensor for the quantification of HER2-ECD was developed. The MIP was electropolymerized by cyclic voltammetry using a solution containing phenol and HER2-ECD on a screen-printed gold electrode (AuSPE). The sensor was characterized by cyclic voltammetry and electrochemical impedance spectroscopy. The analysis of HER2-ECD was performed by differential pulse voltammetry using ([Fe(CN)6]3−/4−as redox probe. The linear range was established in the concentration interval from 10 to 70 ng/mL HER2-ECD, with a limit of detection of 1.6 ng/L and a limit of quantification of 5.2 ng/mL. Through the analysis of other protein biomarkers, the MIP sensor was found to be selective. Furthermore, these proteins did not interfere in the analysis of the selected biomarker. The developed sensor was used for the analysis of spiked human serum samples, providing adequate recovery values and precise results. The outcomes of this study indicate that the developed MIP sensor could be useful in the non-invasive analysis of HER2-ECD in breast cancer patients.